O confisco sem condenação penal como medida de recuperação dos bens e valores instrumentos ou produtos da lavagem de ativos - Rosa, Rafael Arouca [UNESP] (2015)
In order to analyze the political criminology viability and the legitimacy of incorporating the non-conviction based asset forfeiture to brazilian law, this study comprehends the institute as he is involved in the current stage of the globalization process of the societies, in which organized crime, money laundering and other serious criminal offenses are risks not only to the economy but for the institutions in general as they use the innovations implemented in the areas of communications and computing technology. It starts with the elaboration of an overview of the laundering of illicit assets in national and international contexts, based on the brazilian legal system and the main international documents, which states the importance of the recovery of goods and values and the international cooperation for asset recovering; passes by the analysis of the main strategies focused on the recovery of these assets, especially the confiscation, which ceases to be a secondary tool to be seen as fundamental. Next, it discusses the characteristics of the recuperation of assets model and its compatibility with the Federal Constitution and the brazilian legal system, with prominence for the law of non-conviction based asset forfeiture. Thus, the study gives special attention to the main international treaties and conventions, the relevant national legislation and the experiences of other countries in where non-conviction based asset forfeiture is applied, aiming to identify trends and conclusions on a possible brazilian experience